Baryon-number-violating nucleon decays in ALP effective field theories - Tong Li; Michael A. Schmidt; Chang-Yuan Yao (Journal of High Energy Physics)
Abstract The search for baryon-number-violating (BNV) nucleon decay is an intriguing probe of new physics beyond the SM in future neutrino experiments with enhanced sensitivity. The dark sector states such as an axion or axion-like particle (ALP) can induce nucleon decays with distinct signature and kinematics from the conventional nucleon decays. In this work, we study the ALP effective field theories (EFTs) with baryon number violation and the impact of light ALP on BNV nucleon decays. We revisit the dimension-8 BNV operators in the extended EFTs with an ALP field a respecting shift symmetry. The low-energy EFT operators with |∆(B – L)| = 2 and |∆(B – L)| = 0 are matched to the baryon chiral perturbation theory. We obtain the effective chiral Lagrangian and the BNV interactions between ALP and baryons/mesons. The ALP interactions lead to two-body baryon decays B → ℓ (or ν) a and three-body nucleon decays N → M ℓ (or ν) a. We obtain the constraints on the UV scale from the invisible Λ0 decay search at BESIII, the invisible neutron decay search at KamLAND and proton decay search at Super-K. We also show the projections of some other baryon/nucleon decays and present the distinct distributions of kinematic observable.